STRATEGI KOMUNIKASI MELALUI METODE NLP (NEURO LINGUSTIC PROGRAMMING) DALAM PENYULUHAN PENYALAHGUNAAN NARKOBA KEPADA REMAJA DI DENPASAR SELATAN - Putu Soni Kurniawan; I Dewa Ayu Hendrawathi Putri; I Nyoman Alit Putrawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The Drug abuse problems are increasingly apprehensive, the prevalence rate shows that from year to year the number of drug abusers tends to increase. Data from the National Narcotics Board of the Republic of Indonesia states that in 2022 there will be approximately 5 million drug users in Indonesia. From the background of these problems, the researcher is interested in researching